1975
DOI: 10.1063/1.321663
|View full text |Cite
|
Sign up to set email alerts
|

Growth of a smectic A from a bent nematic phase and the smectic light valve

Abstract: We show that for certain liquid crystals, characterized by very small nematic/smectic−A latent heats, the transition from a nematic phase, held firmly in a bent state, to a smectic−A phase takes place via an intermediate state which is stable in a given temperature range and which we have called ’’striped texture’’. This state consists of a corrugated layer of bent nematic which is sandwiched between two smectic−A layers whose planes are oriented in two different directions. As the temperature of the sample is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
41
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(45 citation statements)
references
References 22 publications
4
41
0
Order By: Relevance
“…The resulting frustration phenomenon leads to a characteristic striped pattern sometimes referred to as 'oily streaks' or 'striations', which has been found in several previous studies of flat samples with antagonistic boundary conditions. We however note that the striped pattern can be classified into two types depending on if the striations are along 24 or perpendicular 25,26 to the projected c director field (further details will be discussed in a separate paper). As seen in Fig.…”
Section: Configuration 1: Homeotropic Interior Planar Exteriormentioning
confidence: 99%
See 2 more Smart Citations
“…The resulting frustration phenomenon leads to a characteristic striped pattern sometimes referred to as 'oily streaks' or 'striations', which has been found in several previous studies of flat samples with antagonistic boundary conditions. We however note that the striped pattern can be classified into two types depending on if the striations are along 24 or perpendicular 25,26 to the projected c director field (further details will be discussed in a separate paper). As seen in Fig.…”
Section: Configuration 1: Homeotropic Interior Planar Exteriormentioning
confidence: 99%
“…along c(r, φ , θ ), corresponding to the observations of stripes along c(x, y) in the flat hybrid samples studied by Cladis and Torza. 24 They found that the director bend is initially compressed to an increasingly thin layer within the sample bulk that remains in a nematic state due to a depression of the phase transition temperature induced by the bend distortion. In order to minimise the distortion this internal nematic layer buckles in alternating directions (Fig.…”
Section: Configuration 1: Homeotropic Interior Planar Exteriormentioning
confidence: 99%
See 1 more Smart Citation
“…This important result for a closed form of the generating curve is derived, based on the competition between anchoring and magnetic energy, mediated by elasticity (1) under the global geometric constraint of equidistant layers (4), rather than assumed a priori as in refs. [6,7,18]. To obtain a spacefilling two dimensional structure we perform a parallel transport of the generating curve ζ 0 (ξ) along its normal ν = ν x e x + ν z e z (see Fig.…”
Section: Kχab 2 Wamentioning
confidence: 99%
“…In contrast, patterns in smectic LC phases are more difficult to describe due to the additional one-dimensional positional order. Many, sometimes rather complex, smectic patterns have been observed, such as undulations of the smectic layers in an applied magnetic field (HelfrichHurault instability) [1,3] or other periodic structures, like stripes [6,7], squares [8], or hexagons [9]. Usually, those structures are explained by the formation of focal conic domains or curvature walls, characterized by one typical length scale [3,[10][11][12].…”
mentioning
confidence: 99%